The Golden Age (1975–1986) - Bokov, Andrey; Berzhinsky, Yurii; Kolesnikov, Alexander; Stegaylo, Vladimir; Zhukovsky, Nikolai; Astrakhantseva, Victoria; Studennikov, Alexander (project baikal, 2015)
The Institute had grown up by its tenth anniversary. It had become more significant in the development policy of Irkutsk and the Irkutsk region. Party officials had to reckon with the Institute. It was widely recognized domestically and internationally. None of its leaders had any special training in management. Basing on their intuition and personal experience and being creative and highly professional people, they found and realized principles of effective management of a creative team. This was the second decade and the golden age of Irkutskgrazhdanproject.